Association of Serum Cyclophilin A Levels with Severity of Coronary Artery Disease - Manaswini, Namilakonda; Sreedevi, Neelam N.; Thummala, Sabitha; Saibaba, Kompella S.S.; Mohammed, Noorjahan; Satish, Oruganti Sai (Journal of Laboratory Physicians, 2022)
Objective The disequilibrium between oxidant and antioxidant systems causes oxidative stress. Further, it disrupts the cell and releases reactive oxygen species (ROS), which in turn damages the vascular functions. Cyclophilin A (CypA), an immunophilin, is released in a highly regulated manner from vascular smooth muscle cells and multiplies the deleterious effects of ROS, associated with cardiovascular diseases. Thus, the aim of the present study is to correlate serum CypA levels with the severity of coronary artery disease (CAD).Materials and Methods Study participants composed of 103 adult subjects, among whom 73 subjects were cases who were diagnosed as CAD angiographically. Thirty years of age and gender-matched subjects were taken as controls. The cases were further divided into single, double, and triple vessel disease subgroups. Blood samples were collected for the estimation of serum CypA, malondialdehyde (MDA), high-sensitive C-reactive protein (hsCRP), lipid profile, and plasma-glycated hemoglobin (HbA1C) by relevant biochemical methods.Statistical Analysis The analysis was done using SPSS version 25. The data were expressed as median/mean and interquartile range/standard error. The groups were compared using the Mann–Whitney U-test and the Kruskal–Wallis test. p-Value less than 0.05 was considered statistically significant. Comparison of area under the curve (AUC) in receiver operating characteristic (ROC) curves was performed. A correlation was done by Spearman rank correlation.Results The mean levels of serum CypA, hsCRP, and MDA in cases were significantly higher than those of controls (38 vs. 27 ng/mL, 18 vs. 5.1 mg/L, and 26 vs. 14 nmol/mL, p < 0.001). A positive correlation was observed between serum levels of CypA versus hsCRP and CypA versus MDA (r = 0.36 p = 0.00, r = 0.52, p = 0.00). At cut-off values greater than 33 ng/mL and 2.1 mg/L, serum CypA and hsCRP have 71% sensitivity, 93% specificity (AUC = 0.83), 84% sensitivity, and 70% specificity (AUC = 0.78) respectively. The number of occluded vessels was positively correlated with both CypA and hsCRP. Also, Serum CypA showed a significant positive correlation with HbA1C.Conclusion Serum CypA can be used as a valuable biomarker for CAD.
Keywords: cyclophilin A; hsCRP; malondialdehyde; coronary artery disease; sensitivity; biomarker